Death Scene Reconstruction Through Bloodstain Pattern Analysis on a Complex Suicide Case - Arslan, Murat Nihat; Özbay, Mehmet; Şam, Bülent (The Bulletin of Legal Medicine, 2017)
Using two different methods for suicide, which are usually dangerous-enough for death singly shows the consistency of the desire of death. A 40-year-old man hung himself by shooting through the heart with a converted blank-cartridge gun. Autopsy findings, crime scene investigation findings, bloodstains on the body and the scene made us think that the manner of the death was the suicide.Determining the manner of the death on complex suicide cases should be done before the autopsy with the contribution of crime scene findings. Handling the crime scene findings with a multidisciplinary aspect, considering every object or evidence on the crime scene as a useful tool to solve the case, may facilitate to determine the manner of death. Similarly, when approaching to the deceased at the autopsy room, examination and documentation of bloodstains on the clothes or on the body may provide useful information on determining the manner of the death.
Keywords: complex suicide; hanging; converted blank cartridge gun wound; bloodstain pattern analysis; manner of death